2018
DOI: 10.1016/j.jsv.2018.02.010
|View full text |Cite
|
Sign up to set email alerts
|

Free vibration of functionally graded beams and frameworks using the dynamic stiffness method

Abstract: The free vibration analysis of functionally graded beams (FGBs) and frameworks containing FGBs is carried out by applying the dynamic stiffness method and deriving the elements of the dynamic stiffness matrix in explicit algebraic form. The usually adopted rule that the material properties of the FGB vary continuously through the thickness according to a power law forms the fundamental basis of the governing differential equations of motion in free vibration. The differential equations are solved in closed ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
27
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 91 publications
(31 citation statements)
references
References 43 publications
2
27
0
Order By: Relevance
“…The model accommodates (a) the role of size-effect through the MCST, (b) the lateral inertial effect in the axial vibration via the Rayleigh–Love (RL) theory and (c) the bending moment-induced/shear deformation effects in the transverse vibration. The combination of the RL theory with the shear deformable beam theory is motivated by two recent studies (Banerjee and Ananthapuvirajah, 2018, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…The model accommodates (a) the role of size-effect through the MCST, (b) the lateral inertial effect in the axial vibration via the Rayleigh–Love (RL) theory and (c) the bending moment-induced/shear deformation effects in the transverse vibration. The combination of the RL theory with the shear deformable beam theory is motivated by two recent studies (Banerjee and Ananthapuvirajah, 2018, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…The stiffness matrix is partitioned to separate the actions associated with two ends of the member. 33 In this study, lead rubber bearing (LRB) system was selected as a BI. 34 The geometry of an LRB is shown in Figure 1.…”
Section: Structural Molding Specificationmentioning
confidence: 99%
“…The stiffness matrix is partitioned to separate the actions associated with two ends of the member. 33…”
Section: Modelingmentioning
confidence: 99%
“…In recent years, an elegant modeling method called the dynamic stiffness method (DSM) [25] has been well developed and widely used in vibration analysis of beams, plates and shells structures [26][27][28][29][30][31][32][33][34][35][36]. In the DSM, the frequency-dependent shape functions are derived directly from the governing equation.…”
Section: Introductionmentioning
confidence: 99%
“…However, not all kind of structures can obtain exact shape function from the governing equation. us, the DSM is mostly used in one-dimensional structure like beams [26,27] and Levy-type plate [37]. Until the last few years, it is reported that the DSM has been used to establish the dynamic model of rectangular plate with general boundary conditions [38,39].…”
Section: Introductionmentioning
confidence: 99%